Integrative analysis and expression profiling of secondary cell wall genes in C4 biofuel model Setaria italica reveals targets for lignocellulose bioengineering - Muthamilarasan, Mehanathan; Khan, Yusuf; Jaishankar, Jananee; Shweta, Shweta; Lata, Charu; Prasad, Manoj (Frontiers in Plant Science, 2015)
Several underutilized grasses have excellent potential for use as bioenergy feedstock due to their lignocellulosic biomass. Genomic tools have enabled identification of lignocellulose biosynthesis genes in several sequenced plants. However, the non-availability of whole genome sequence of bioenergy grasses hinders the study on bioenergy genomics and their genomics-assisted crop improvement. Foxtail millet (Setaria italica L.; Si) is a model crop for studying systems biology of bioenergy grasses. In the present study, a systematic approach has been used for identification of gene families involved in cellulose (CesA/Csl), callose (Gsl) and monolignol biosynthesis (PAL, C4H, 4CL, HCT, C3H, CCoAOMT, F5H, COMT, CCR, CAD) and construction of physical map of foxtail millet. Sequence alignment and phylogenetic analysis of identified proteins showed that monolignol biosynthesis proteins were highly diverse, whereas CesA/Csl and Gsl proteins were homologous to rice and Arabidopsis. Comparative mapping of foxtail millet lignocellulose biosynthesis genes with other C4 panicoid genomes revealed maximum homology with switchgrass, followed by sorghum and maize. Expression profiling of candidate lignocellulose genes in response to different abiotic stresses and hormone treatments showed their differential expression pattern, with significant higher expression of SiGsl12, SiPAL2, SiHCT1, SiF5H2 and SiCAD6 genes. Further, due to the evolutionary conservation of grass genomes, the insights gained from the present study could be extrapolated for identifying genes involved in lignocellulose biosynthesis in other biofuel species for further characterization.